1981
DOI: 10.1017/s1742758400000618
|View full text |Cite
|
Sign up to set email alerts
|

Biology and control of Culex pipiens quinquefasciatus Say, 1823 (Diptera, Culicidae) with special reference to Africa

Abstract: This paper is an attempt to synthesize information available on C. p. quinquefasciatus in Africa. The latter is presently found in most urban areas of the African continent and in rural settlements which show some trends towards urbanization. In East Africa, and the islands of the Indian Ocean, C. p. quinquefasciatus is one of the major natural vectors of Wuchereria bancrofti. In addition it can also transmit, under laboratory conditions, some other pathogenic agents.Preimaginal forms develop in different kind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 51 publications
2
72
0
3
Order By: Relevance
“…For example Mahanta et al (1999) found peaks around 19.00 and 23.00h; Yee and Foster (1992) found peaks at 23.00h and before dawn, while Sucharit et al (1981) found three peaks. The fact that gravid females, which are likely to be looking for oviposition sites, had dawn and sunset peaks corresponds to the results of oviposition behaviour observations by Hayes and Downs (1980) and Subra (1981). However, other studies have shown considerable differences from this pattern.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…For example Mahanta et al (1999) found peaks around 19.00 and 23.00h; Yee and Foster (1992) found peaks at 23.00h and before dawn, while Sucharit et al (1981) found three peaks. The fact that gravid females, which are likely to be looking for oviposition sites, had dawn and sunset peaks corresponds to the results of oviposition behaviour observations by Hayes and Downs (1980) and Subra (1981). However, other studies have shown considerable differences from this pattern.…”
Section: Discussionsupporting
confidence: 82%
“…Some studies have found that biting activity of Cx quinquefasciatus was greatest in the early part of the night (Gowda and Viayan, 1993;Khan et al, 1997;Pipitgool et al, 1998), while others found activity greatest after midnight (Brunhes, 1975;Subra, 1981;Vanamail and Ramaiah, 1991;Ramasamy et al, 1994;Chandra, 2001). In still other studies, however, two peaks of activity were recorded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The service [26] observed that peaks of biting by C. pipiens quinquefasciatus took place from March to May (late dry to early wet season) and in September (late wet season) in northern Nigeria. Peaks in female mosquito densities were in the rainy season and at the beginning of dry season in urban areas in Upper Volta [27], in rural areas [28], and in the beginning of the rainy season in Kaduna, northern Nigeria [26]. The mean densities in West Africa in the rainy season are often ten times as high as dry season densities [27].…”
Section: Abundance and Seasonalitymentioning
confidence: 99%
“…Peaks in female mosquito densities were in the rainy season and at the beginning of dry season in urban areas in Upper Volta [27], in rural areas [28], and in the beginning of the rainy season in Kaduna, northern Nigeria [26]. The mean densities in West Africa in the rainy season are often ten times as high as dry season densities [27].…”
Section: Abundance and Seasonalitymentioning
confidence: 99%